Synthesis of Some Novel Imidazolinone Derivatives withDibenzo(b,f)azepine Nucleus - V. Bhatt, Pralav; N. Wadia, Devang; M. Patel, Rajni; M. Patel, Pravin (Asian Journal of Chemistry, 2010)
4-Arylidene-2-phenyl-5-(4H)-oxazolones (1a–j) were prepared by Erlenmeyer condensation. The 4-arylidene 2-phenyl-5-(4H)-oxazolones react with p-phenylene diamine in presence of dry pyridine to give corresponding 3-(4-amino-phenyl)-5-benzylidene-2-substituted phenyl-3,5-dihydro-imidazol-4-one (2a–j); this was further reacted with dibenzo (b,f) azepine-5-carbonyl chloride (3) in basic medium to give dibenzo(b,f)azepine-5-carboxylic acid [4-(4-substituted-5-oxo-2-phenyl-4,5-dihydro-imidazol-1-yl)-phenyl] amide (4a–j). The constitution of the selected products has been supported by elemental analysis, infrared spectra and nothing sup 1H NMR spectra. The purity of the compounds was checked by thin layer chromatography.